2017
DOI: 10.1021/acs.jctc.7b00944
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Changes in Neurolysin Dynamics Upon Inhibitor Binding

Abstract: Crystal structures of neurolysin, a zinc metallopeptidase, do not show a significant conformational change upon the binding of an allosteric inhibitor. Neurolysin has a deep channel where it hydrolyzes a short neuropeptide neurotensin to create inactive fragments and thus controls its level in the tissue. Neurolysin is of interest as a therapeutic target since changes in neurotensin level have been implicated in cardiovascular disorders, neurological disorders, and cancer, and inhibitors of neurolysin have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
(99 reference statements)
0
16
0
Order By: Relevance
“…Recently, our violin model has been used to understand dynamics‐based allostery in protein families other than kinases. Examples include exploration of red light–sensing bacteriophytochromes associated with cyclic dimeric guanosine monophosphate–producing diguanylyl cyclases and the zinc metallopeptidase neurolysin .…”
Section: Dynamics‐based Allosterymentioning
confidence: 99%
“…Recently, our violin model has been used to understand dynamics‐based allostery in protein families other than kinases. Examples include exploration of red light–sensing bacteriophytochromes associated with cyclic dimeric guanosine monophosphate–producing diguanylyl cyclases and the zinc metallopeptidase neurolysin .…”
Section: Dynamics‐based Allosterymentioning
confidence: 99%
“…LDA yields a classification vector—analogous to collective variables in principal component analysis—that results in the largest differences between the classes, while maintaining small differences within the classes. 51 , 52 This has been recently used to analyze molecular simulations, 33 , 53 including to determine collective variables for enhanced sampling simulations. 54 , 55 As there are only two classes during training here (“apo” and “complex”), the analysis yields only one LDA vector.…”
Section: Resultsmentioning
confidence: 99%
“…The extracellular domain of ACE2 is homologous to other metallo-peptidases such as ACE, 30 carboxypeptidase Pfu, 31 and neurolysin, 32 which all share the characteristic “clam shell” structure. Neurolysin dynamics were studied in detail in our previous work 33 using MD simulations and the linear discriminant analysis (LDA) machine learning method. Our findings compared contact networks of the apo neurolysin and neurolysin bound to an allosteric inhibitor and pinpointed several differences that were far from the inhibitor-binding site, which suggests long-range allosteric behavior in metallo-peptidases.…”
Section: Introductionmentioning
confidence: 99%
“…The search for a modulatory site was carried out in the hinge region because crystal structures of both Nln and ACE2 demonstrate that catalysis is accompanied by large hinge-bending motions (Brown et al, 2001;Towler et al, 2004). The hinge region in both peptidases can affect the distance between the two structural domains and by that modulate substrate binding and catalysis (Ray et al, 2004;Towler et al, 2004;Uyar et al, 2018). Several surface pockets with adequate solvent accessible volumes (DSSP (Kabsch and Sander, 1983) and castP (Dundas et al, 2006)) were identified in the hinge region of Nln.…”
Section: Resultsmentioning
confidence: 99%